Evaluasi Proses Bisnis Bagian Produksi Dengan Metode Quality Evaluation Framework (QEF) Studi Pada CV. Kajeye Food - Yusuf Reyhan Aditiawan; Aditya Rachmadi; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
CV. Kajeye Food is a company that originated from a home company engaged in the production of fruit processing, especially chips and fruit sweets with the brand SoKressH is in Malang. In the production process, there are several things that the company needs to consider, such as the efficiency of raw materials and workers used. There are some mistakes that occur as in the process of raw material processing, the quality of the raw materials ordered is sometimes not in accordance with the company's preset standards. In addition there is a problem that the absence of regular machine maintenance routine/scheduling, cleaning and checking of the machine is done when it is needed to cause unexpected engine damage and resulting production process Stalled. Therefore, evaluation of business processes in progress using the Quality Evaluation Framework (QEF) aimed at evaluating the quality of business processes is objective, quantitative and by fact. As well as the Failure Mode And Effect Analyst (FMEA) method to evaluate and search for root problems to find out which problems have higher levels of urgency. And identify the problems that have been defined in the QEF and FMEA methods using the Fishbone method. Business process evaluation can be used by the company to compare the business targets made before the activity begins with the end result of the business activities.problems to find out which problems have higher levels of urgency. And identify the problems that have been defined in the QEF and FMEA methods using the Fishbone method. Business process evaluation can be used by the company to compare the business targets made before the activity begins with the end result of the business activities.